The mediating effect of corporate social responsibility on the relationship between corporate governance and financial performance. (c2016) - AlKassar, Abdul Rahman (2016)
Over the years, corporations have concentrated their efforts on increasing the effectiveness of their governance practices. In an attempt to decrease risk while ensuing higher returns to shareholders, corporations made efforts to measure such practices. Also, corporations focused on the financial performance of how their earnings respond to diverse managerial policies. Recently, there have been rising pressures on corporations to practice corporate social responsibility (CSR). The issue of whether or not corporations that are actively involved in CSR will operate and perform better has been heavily debated. This raises the question of whether improvement in financial performance can be a result of CSR practices implemented by the firm. This study examines the associations among corporate governance, corporate social responsibility and financial performance. In particular, this study explores the possible mediating effect of CSR on the aforementioned relationship. Empirical evidence of this quantitative study confirmed the significance of the relationships as well as the mediating effects of CSR.